Perceptions of Teachers and Students of Vocational High Schools on the Learning Model of PAI Based on Preparation for the World of Work - Ilyasa, Faisal Fauzan; Supriadi, Udin; Firmansyah, Mokh Iman; oʻgʻli, Sodiqov Ulugʻbek Gʻulomjon (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
Islamic Religious Education (PAI) plays an important role in shaping the akhlak and character of students, especially in the context of Vocational High Schools (SMK) that prepare students for the world of work. However, PAI learning in SMK is often still theoretical and less relevant to industrial needs. This study aims to examine teachers' and students' perceptions of a PAI learning model oriented toward work-readiness at SMK ICB Bandung. Using a qualitative approach with a case study design, data were collected through in-depth interviews, classroom observations, and document analysis. The results of a word frequency query using NVivo 12 showed that akhlak aspects were the primary concern in PAI learning, with the highest frequency of occurrence in the interviews. Both teachers and students view akhlak such as honesty, responsibility, discipline, and work ethic—as fundamental components of character that directly support readiness to enter the workforce. Learning models applied include Problem-Based Learning (PBL), Project-Based Learning (PjBL), Discovery Learning, and approaches such as Uswah Hasanah and Ibrah Mauidzah. However, implementation still faces challenges, such as limited teacher experience with industrial contexts, lack of facilities, and overly theoretical teaching methods. Students express a desire for more interactive, practice-oriented, and industry-relevant learning models that integrate Islamic values into work simulations and Islamic soft-skills training. Therefore, innovation is needed to develop a more applicable PAI learning model, including the use of digital technologies and improved teacher competence in understanding the demands of the professional world.